Estuarine intertidal meiofauna and nematode communities as indicator of ecosystem's recovery following mitigation measures. (July 2015) - Alves, A.S.; Caetano, A.; Costa, J.L.; Costa, M.J.; Marques, J.C.
Highlights: Meiobenthic communities were analyzed along an estuarine gradient of eutrophication. Seasonal variation was observed with no reflection of the eutrophication gradient. Structure and function of the nematode's communities revealed no spatial differences. Evidences of the system's recovery after mitigation measures can be highlighted. Abstract: The Mondego estuary (Portugal) has been under environmental pressure since the early 1990s due to different anthropogenic stresses. The system has been studied following benthic communities' features from an impacted situation until the recovery phase, focusing mostly on macrobenthos. Following the application of mitigation measures in the estuary, this study is focused on the variability of the intertidal meiobenthic and nematode communities in a system that has recovered after different anthropogenic stresses. While at the spatial level (among areas along the eutrophication gradient) no significant differences were observed regarding the structure and function of the nematode communities, at the seasonal level some differences stood out. These results broadly suggest that the system has recovered from the early situations of pressures being, to the best of our knowledge, the first attempt to investigate the variability of intertidal meiobenthic and nematode communities in the scope of a system's recovery along an estuarine gradient of eutrophication. Even if performed in a short timeline, this study provides a good baseline analysis of conditions, being important for future comparisons.